Going there : Black visual satire - Powell, Richard J. (Yale University Press in association with the Hutchins Center For African & African American Research, Harvard Univeristy, 2020)
"More than a one-liner" -- Drawing the color line : the art of Ollie Harrington -- The minstrel strain -- Robert Colescott : between the heroic and the ironic.